On the development of a sustainable and fit for the future transportation network. - Markvica, Karin; Prandtstetter, Matthias; Hu, Bin; Ritzinger, Ulrike; Zajicek, Jürgen; Berkowitsch, Claudia; Hauger, Georg; Pfoser, Sarah; Berger, Thomas; Eitler, Sandra; Schodl, Reinhold (My University, 2018)
Population growth in cities and expanding city territory as well as population decline in rural areas pose a challenge for the existing transport network. As a consequence, we observe a rapid change in transport infrastructure and transportation technology within the last few years. The development of individually moving drones, for example, reached a new climax with novel applications such as the trial parcel distribution in rural areas in Great Britain and Germany or medicine distribution in Rwanda, Africa. At the same time, there are advancements with respect to land-borne transportation technology, among them the Hyperloop concept presented by SpaceX and Tesla founder Elon Musk with the first test of a prototype propulsion system in May 2016 and the first test on tracks in May 2017, both carried out by Hyperloop One. Due to the novelty or differentness, it will initially be challenging to integrate them into the existing network and to identify suitable corridors leading to especially beneficial effects on the overall transport network. While TEN-T and the national guidelines already present plans for further development in the transport sector, these strategy papers only provide for existing technologies and therefore have a limited extend. The effects of new technologies and (high-performance) infrastructures are furthermore hardly examined at the moment, although the first test tracks are already being under discussion or even build (for the example of Hyperloop). At present, it remains unclear how these novel transportation technologies will change society, our understanding of spatial proximity, mobility and consequently the logistics sector. In this work, we give an overview regarding first considerations and reflections on the impacts of the changes and developments in the field of freight transportation. The results presented in this work are based on the outcomes of the research project inned (innovative network design) funded by the Austrian federal ministry for transport, innovation and technology (bmvit). Established as an exploration study, the project mainly focusses on the estimation of the impacts of high-performance transportation technologies on the society, spatial proximity and the logistics sector in the course of extending the European transportation network accordingly. In our understanding, we refer to high-performance transportation technologies as mobility systems with either high throughput (fast and/or high utilization loads) or very flexible application. Concrete, we focus in our work on Hyperloop technologies, Cargo-Sous-Terrain, freight airships and drones. Although the mobility system is considered in its entirety, the main focus is on freight transportation. We investigate the technological boundaries with respect to network design set by the above mentioned high-performance transportation technologies as a first step. Then, a societal assessment is carried out taking spatial, social, economic and environmental aspects into account. Constraints imposed by technology and society are considered when planning an exemplary future European transportation network based on actual (freight) transportation demand. Conclusions are drawn on additional research and development activities that have to be performed in order to reach a sustainable, reliable and fit for the future European transportation network. Further, we report on expected effects of high-performance transportation technologies on geographical proximity and therefore the change in meaning of the term region . Finally we show preliminary results on the integration of high-performance transportation technologies into existing transportation networks for some exemplary corridors.
Keywords: Verkehrsinfrastruktur; Verkehrsnetz; Verkehrstechnologie; Güterverkehr; Mobilität; Gesellschaft